KAJIAN KOMODITAS UNGGULAN SUB-SEKTOR PERKEBUNAN DI PROVINSI JAMBI - Siti Abir Wulandari; Nida Kemala (Universitas Batanghari Jambi, 2016)
The objective of this research is to know the latest ten years description and the differenceinvolving the contribution of estate sub-sector toward to Gross Domestic Product (GDP) in Jambi Province, the estate prime commodities potential. Literature study method was used that completed by descriptif analization. The result of this research showed that in the latest ten years indicated that there was an increasing contribution of estate sub-sector toward to Gross Domestic Product (GDP) in Jambi Province, although there wa a little deceasing in 2008. the average of rubber land area (646,707 H) was bigger than palm oil one (514,065 H). the average og rubber productivity (5,7%) was lower then the palm oil (0,75%). the average rubber annually was 803 kg/H lower than that I Malaysia (1,3 ton/ha) dan Thailand (1,9 ton/ha). the palm oil productivity was 3,341 ton /H was still below the ideal productivity (6 ton/H). the last showed that the production growth of oil palm (6% per year) was higher than rubber (3% per year). Beside there was a significant deference among the latest ten year contribution, with a note the its average was 14,3 per year.Key word : Contribution, potential, Rubber, Oil Palm